1987
DOI: 10.1128/aac.31.8.1281
|View full text |Cite
|
Sign up to set email alerts
|

Plasmids and resistance to antimicrobial agents in Aeromonas sobria and Aeromonas hydrophila clinical isolates

Abstract: The antimicrobial susceptibilities of 75 Aeromonas isolates were determined by agar dilution. Differences in resistance patterns were observed between strains isolated from different geographic locations and between A. sobria and A. hydrophila isolates. Multiple resistance was common; however, only one conjugative plasmid was detected. This 110-megadalton plasmid mediated resistance to eight antibiotics.The motile aeromonads are recognized both as causes of infection in immunocompromised patients and as enteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 18 publications
5
35
0
1
Order By: Relevance
“…Most of the tested strains carried several plasmids, including some with a high molecular weight. However, no correlation was found between the number of antibiotic resistance markers and the number of plasmid bands, as previously reported (15), suggesting that most of these plasmids either encoded characters other than antibiotic resistances or were cryptic (13). In enterobacteria, resistances which are known to be exclusively (quinolones) or mainly (fosfomycin) due to mutations were found to be chromosomally located.…”
Section: Discussionmentioning
confidence: 55%
“…Most of the tested strains carried several plasmids, including some with a high molecular weight. However, no correlation was found between the number of antibiotic resistance markers and the number of plasmid bands, as previously reported (15), suggesting that most of these plasmids either encoded characters other than antibiotic resistances or were cryptic (13). In enterobacteria, resistances which are known to be exclusively (quinolones) or mainly (fosfomycin) due to mutations were found to be chromosomally located.…”
Section: Discussionmentioning
confidence: 55%
“…Local selective pressures can influence the antibiotic resistance. Chang and Bolton (1987) found that more percentage of Asian isolates of A. hydrophila were resistant to tetracycline and rifampicin than Australian isolates. More than 50% of the A. hydrophila strains was resistant to tetracycline and occurrence of tetracycline resistant strains of A. hydrophila from different sources was reported (Ansary et al, 1992;Ramteke et al, 1993;Pettibone et al, 1996;Son et al, 1997;Kampfer et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…(33,82) and Plesiomonas shigelloides (83). Plasmids have also been reported in Vibrio cholerae (160).…”
Section: Other Enteric Bacteria and Miscellaneousmentioning
confidence: 99%